Most Malawian maize and soybean farmers sell below official minimum farmgate prices - Baulch, Bob; Ochieng, Dennis O. (International Food Policy Research Institute, 2020)
This note analyzes the prices received by 1,048 maize and 1,265 soybean farmers in Malawi during the main harvest marketing season of 2020. Between April and July, whenever they sold maize or soybeans, farmers were asked to report the prices they received by calling or texting a toll-free number managed by Farm Radio Trust. Reported prices were then compared to the minimum farmgate prices set by the Ministry of Agriculture and Food Security. Our findings show that 76 percent of maize farmers and 90 percent of soybean farmers sold their crops at below the official minimum farmgate prices. On average, prices received by these farmers were approximately three-quarters of official minimum farmgate prices.